New or little-known jewel beetles on mistletoe, Taxillus Tiegh. (Loranthaceae), in Japan: Unusual morphology and biology in Habroloma Thomson, 1864 (Coleoptera: Buprestidae) - Tamadera, Yutaka (Zootaxa, 2025)
Habroloma (Parahabroloma) tsutsumiuchii sp. nov., a new jewel beetle species associated with mistletoe, Taxillus yadoriki (Siebold ex Maxim.) Danser (Loranthaceae), is described from Honshu and Kyushu in Japan. Additionally, information on the morphology of H. (P.) taxillusi Kato & Kawakita, 2023, associated with T. yadoriki, is revised based on more than 50 specimens; a first description of the genitalia, new distributional records within Japan, and notes on mistakes in the labeling of the type specimens and in the clypeus description are given. Information on the biology of the two mistletoe-associated buprestid species, especially in the leaf-mining habit, is also reported in detail. This study reveals that the two species have peculiar morphological and biological characters that are unique or rare within Habroloma: 1) modified antennal scape with distinct sexual dimorphism; 2) prominently narrowed clypeus; 3) elytral round hole puncture; 4) pronotal and elytral setal tufts; 5) hypomeral apical excavation; 6) apical comb of female abdomen; 7) delta-like portion of leaf-mine; 8) frass pupal chamber; and 9) large clutch size. Moreover, distributional differences between the two species are discussed, and the association of jewel beetles with mistletoe is reviewed using a tentative species checklist.